2023
DOI: 10.1002/ijgo.15095
|View full text |Cite
|
Sign up to set email alerts
|

Interconnection between reproductive and migrant health rights

Saverio Bellizzi,
Alessandra Nivoli

Abstract: SynopsisCritical policies are needed, in line with the universal health coverage agenda, for the inclusion of migrant women recently impacted by restrictions in accessing abortion care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to data from the National Bureau of Statistics of China, in 2020, the total number of minority migrants nationwide reached 33.71 million, an increase of 25.47 million compared to the year 2000, representing a staggering growth of 309.1%. Due to the risks associated with frequent mobility, the vulnerability of migrant employment, the challenges of urban integration, and the continuity of social security, minority migrants are prone to health risks [ 1 3 ]. Previous studies have found that the quantity and quality of public health services provided to rural migrants are insufficient, leading to serious concerns about their health conditions [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to data from the National Bureau of Statistics of China, in 2020, the total number of minority migrants nationwide reached 33.71 million, an increase of 25.47 million compared to the year 2000, representing a staggering growth of 309.1%. Due to the risks associated with frequent mobility, the vulnerability of migrant employment, the challenges of urban integration, and the continuity of social security, minority migrants are prone to health risks [ 1 3 ]. Previous studies have found that the quantity and quality of public health services provided to rural migrants are insufficient, leading to serious concerns about their health conditions [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies further explore the influencing factors of health service utilization rates among mobile people, including minority rural migrants. From the persrpective of public service policies themselves, whether health service projects are charged has a complex impact on the coverage, utilization rates, and social costs of health services [ 3 , 26 , 27 ]. In comparison to the abundant literature focusing on the utilization and influencing factors of public health services, there is relatively less research on the impact of health rights accessibility.…”
Section: Introductionmentioning
confidence: 99%